The Impact of Horizontal Marking on the VisuMax Surgical Bed Headrest on the Outcomes of Myopic Astigmatism Correction With Small Incision Lenticule Extraction - Yun Wang; Xiaofeng Zhang; Wenwen Pan; Li Wang; Jing Lou; Yue Xu (Journal of Ophthalmology)
Conclusions: Augmented by precise preoperative strategies, including headrest marking and fixation training, SMILE achieves astigmatism axis correction efficacy comparable to FS-LASIK. SMILE and FS-LASIK are effective and comparable in correcting moderate-to-high astigmatism, highlighting their safety, efficacy, and predictability as corrective measures for myopic astigmatism.